Human Pythiosis, a Rare Cause of Arteritis: Case Report and Literature Review - Prasertwitayakij N. (2014)
Objective: To present a case of Pythium insidiosum arteritis and review reported cases of human pythiosis. Methods: Search of MEDLINE (PubMed) and the Thai Index Medicus was performed using the words "pythiosis" and "pythium." Search of abstracts from a scientific meeting also was performed. Only reported cases in the English or Thai language, with enough clinical information for analysis, were included. Results: There were a total of 32 cases of human pythiosis, with 31 identified in the literature. Twenty-five cases were Thai. Twenty of 21 patients with known occupations were farmers. There was ocular infection in 9 cases, subcutaneous infection in 5 cases, arterial infection in 17 cases, and cardiopulmonary infection in 1 case. Thalassemia was a common associated finding. In addition to systemic antifungal therapy, surgery was required in most cases. The highest mortality rate was seen in the arteritic form, particularly in patients with arterial lesions proximal to the superficial femoral artery. Conclusions: Human pythiosis is rare. Physicians should be suspicious of pythiosis in individuals, particularly farmers in Thailand, who develop nonhealing cutaneous ulcers or keratitis, which do not respond to conventional treatment. P insidiosum infections should be listed as a rare cause of infectious arteritis. © 2003 Elsevier Inc. All rights reserved.